SINERGI BUDAYA 5R DAN NILAI SIPAKATAU SEBAGAI UPAYA PELESTARIAN NILAI LOKAL MASYARAKAT [SYNERGY OF 5R CULTURE AND SIPAKATAU VALUES AS AN EFFORT TO PRESERVE LOCAL VALUES OF THE BUGIS-MAKASSAR COMMUNITY] - Rahmawati, Rahmawati; Arsyad, Yolandika (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to examine the synergy between the 5R culture (Ringkas, Rapi, Resik, Rawat, and Rajin) and the local values of Sipakatau in creating a disciplined, clean, and character-driven community environment. The 5R culture, derived from a hygiene management approach, was adapted to the local Bugis-Makassar socio-cultural context and combined with Sipakatau values, which emphasize respect for individuals as a moral foundation in community life. This study used qualitative methods, with data collection techniques including online interviews and literature review. The results indicate that the synergy between the 5R culture and Sipakatau values contributes positively to the preservation of local values and encourages active community participation in creating a clean, orderly, and respectful environment. The integration of these two values also forms part of character education based on local wisdom, relevant to supporting sustainable development in the Bugis-Makassar community.